Effectiveness and mechanism of metformin in animal models of pulmonary fibrosis: A preclinical systematic review and meta-analysis - Wu, Xuanyu; Xiao, Xiang; Chen, Xinyu; Yang, Maoyi; Hu, Zhipeng; Shuai, Sijia; Fu, Qinwei; Yang, Han; Du, Quanyu (Frontiers in Pharmacology, 2022)
Background: Pulmonary fibrosis (PF) is a lung disease with no curative drug, characterized by a progressive decrease in lung function. Metformin (MET) is a hypoglycemic agent with the advantages of high safety and low cost and has been used in several in vivo trials to treat fibrotic diseases. Objective: This study aimed to explore the efficacy and safety of MET in treating PF and elaborate on its mechanism. Methods: Eight databases were searched for in vivo animal trials of MET for PF from the time of database creation until 1 March 2022. The risk of bias quality assessment of the included studies was conducted using SYRCLE’s risk of bias assessment. Pulmonary inflammation and fibrosis scores were the primary outcomes of this study. Hydroxyproline (HYP), type I collagen (collagen I), α-smooth muscle actin (α-SMA), transforming growth factor-β (TGF-β), Smad, AMP-activated protein kinase (AMPK), and extracellular signal–regulated kinase (ERK) protein expression in lung tissues and animal mortality were secondary outcomes. Effect magnitudes were combined and calculated using Revman 5.3 and Stata 16.0 to assess the efficacy and safety of MET in animal models of PF. Inter-study heterogeneity was examined using the I2 or Q test, and publication bias was assessed using funnel plots and Egger’s test. Results: A total of 19 studies involving 368 animals were included, with a mean risk of bias of 5.9. The meta-analysis showed that MET significantly suppressed the level of inflammation and degree of PF in the lung tissue of the PF animal model. MET also reduced the content of HYP, collagen I, α-SMA, and TGF-β and phosphorylation levels of Smad2, Smad3, p-smad2/3/smad2/3, ERK1/2, and p-ERK1/2/ERK1/2 in lung tissues. MET also elevated AMPK/p-AMPK levels in lung tissues and significantly reduced animal mortality. Conclusion: The results of this study suggest that MET has a protective effect on lung tissues in PF animal models and may be a potential therapeutic candidate for PF treatment. Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=327285, identifier CRD42022327285.